The Nuruls from a Linguistic Perspective as a Popular Youth Culture in Indonesia (e-Journal of Linguistics, 2025)
In today's digital era, the expansion of language has been rapidly developing, allowing the representation of a word to shift or even for the meaning of that language to change. Moreover, in a language, the concepts of open and closed word classes are recognized, where open word classes are those that will continuously change and expand, while closed word classes are those that are unlikely to ever change or grow. Currently, among young people, the term "The Nuruls" has become popular. This term is derived from the concept of a person's name, even though linguistically, the word "Nurul" comes from Arabic, meaning "Light." Interestingly, the word "Nurul" is preceded by the article "the," which originates from English. The combination of morphemes "the" and "Nurul" creates a unique meaning among young people, indicating a significant shift in meaning. Therefore, the purpose of this research is to examine the semantic shift observed in the phrase "The Nuruls" and to identify the markers that represent this phrase. This study employs a semiotic approach to explore the meaning shift in the phrase "The Nuruls." The research uses a descriptive qualitative method, which is employed to describe the data descriptively, and the analysis will also be presented in a descriptive manner.
Keywords: Pop Culture; Semantics; Meaning; Semiotics